Smoking, occupational exposure to rubber, and lung cancer. - Zhang, Z F (1989)
A cohort of 1624 employees (957 men, 667 women) in a rubber factory in Shanghai have been followed up since 1972 and their 12 year mortality experience is presented. The relative risk of lung cancer for smokers was 8.5 for men and 11.4 for women and for rubber workers exposed to curing agents or talc powder 3.2 for men and 4.6 for women.